Implementation of the Program for Increasing the Role of Women Towards Healthy Prosperous Families (P2WKSS) in Sukabumi City - Nuraeni Nuraeni; Yana Basori; Tuah Nur (Program Pascasarjana Universitas Negeri Makassar, 2023)
The implementation process has stages of the public policy process that need to be implemented in order to achieve the objectives according to the policy plan. The program (P2WKSS) is a program to increase the role of the community that uses a cross-developmental approach pattern, in a coordinated manner directed at improving family welfare in order to achieve a quality standard of living in alleviating poverty. This study aims to determine the implementation of the P2WSKSS Program in Sukabumi City, there are 6 criteria in influencing implementation, namely: 1) Policy standards and objectives, 2) Resources, 3) Inter-organizational communication, 4) Characteristics of implementing agents, 5) Economic Environment, Social and Politics, 6) The attitude of the implementing. The method used is a qualitative method with a narrative approach. Data collection techniques include observation, interviews, documentation, and audio-visual material. The results showed that the implementation was not optimal for several periods, there was a discrepancy in objectives, namely the program was not implemented within 2 years, namely in 2020 & 2021 so there was a significant increase in poverty growth, there was a need for increased guidance for the target community, a lack of carrying out inter-agency monitoring in increasing the role of women existing location and evaluation for program sustainability. Several things must be improved, namely increasing the quality of resources, because it is the executor who is the key to the success of program objectives, it is necessary to improve the approach so that community participation is in accordance with the target.